Hvem styrer fængslerne og fangehåndteringen i Danmark? - Peter Fransen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article analyses how the directors of the Prison and Probation Service have dealt with the treatment of convicted prisoners over the past 111 years. What opinions have they expressed on the issues? What values have they wanted to promote? What influence have they had on the system’s development? These top officials have had to deal with a changing political reality. Furthermore, their position has become increasingly administrative in recent decades with less emphasis placed on their professional perspectives concerning the treatment of convicted prisoners.